1997
DOI: 10.1093/bja/78.1.60
|View full text |Cite
|
Sign up to set email alerts
|

Sevoflurane modulates both GABAA and GABAB receptors in area CA1 of rat hippocampus

Abstract: It has been suggested that volatile anaesthetics enhance synaptic inhibition via gamma-aminobutyric acid (GABA) in the central nervous system. We have examined the effects of sevoflurane on GABAA and GABAB receptors in rat hippocampus in vitro. Extracellular recordings were used to record field potentials in rat CA1 pyramidal neurones of transverse hippocampal slices, stimulated electrically via stratum radiatum input. Sevoflurane 0.4-5.0 vol% decreased the amplitudes of population spikes (PS) of CA1 neurones … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 28 publications
0
22
0
1
Order By: Relevance
“…15 Volatile anaesthetics enhance synaptic inhibition through GABA in the central nervous system (CNS). [16][17][18][19] The precise mechanism by which sevoflurane produces loss of consciousness is unknown. It has been demonstrated that sevoflurane and GABA agonists (muscimol, baclofen) act on different domains of the GABA receptor complex.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Volatile anaesthetics enhance synaptic inhibition through GABA in the central nervous system (CNS). [16][17][18][19] The precise mechanism by which sevoflurane produces loss of consciousness is unknown. It has been demonstrated that sevoflurane and GABA agonists (muscimol, baclofen) act on different domains of the GABA receptor complex.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that sevoflurane and GABA agonists (muscimol, baclofen) act on different domains of the GABA receptor complex. 16,17 It has also been demonstrated that sevoflurane activates at least two distinct domains of the GABA-A receptor, increasing the GABA-ergic transmission by enhancing the affinity of GABA for the GABA receptor and inducing a picrotoxin-mediated antagonism of the GABA-A receptor. 16,17 In the present study, the analeptic role of flumazenil when administered at the end of the surgical procedure was our main interest.…”
Section: Discussionmentioning
confidence: 99%
“…This reversal effect by bicuculline seems unlikely to be involved in a release of a GABA-mediated tonic inhibition, given that 0.1 mg/kg bicuculline in the absence of sevoflurane did not increase nociceptive C responses significantly. Previous studies have revealed that the sevoflurane-induced inhibition of field potentials evoked from CA1 of the hippocampus is partially antagonized by phaclofen, a competitive antagonist of the GABA B receptor [16] . However, the antinocifensive effect of halothane was not affected by the intrathecal administration of GABA B receptor antagonist CGP 35348 [7] .…”
Section: Discussionmentioning
confidence: 99%
“…Hippocampal slices were prepared as previously described [26] . Briefly, brain was rapidly removed, and hippocampus was dissected and sliced transversely to its longitudinal axis (400 µm thick) in cold artificial cerebrospinal fluid (ACSF) with a Rotorslicer DTY-7700 (DSK, Osaka, Japan).…”
Section: Animals and Slice Preparation Sprague-dawley Ratsmentioning
confidence: 99%
“…By phosphorylating specific serine and threonine residues in cellular targets, they affect gene expression, mitosis, cytokinesis, metabolism, and cell death. Many studies demonstrate that modulations of extracellular signal-regulated protein kinases (MEK-ERK1/2, ERK1/2 MAPK) and p38 MAPK activities either by ischemia or by pharmacological agents are important in the genesis of the cytoprotective phenotype [22][23][24][25][26] . To date, no data are available with respect to the role of MAPKs in APC.…”
Section: Introductionmentioning
confidence: 99%